Kolaborasi PSDKU Siak: Peningkatan Fasilitas Bank Sampah Pelangi dengan Cat Ramah Lingkungan - Arya Wieanata; Trisuciati Syahwardini; Hasrul Hasrul; Ni Putu Vidya Primarista; Abdul Rohman Wali (Journal of Social and Community Service, 2025)
Achieving the Sustainable Development Goals (SDGs), particularly SDGs 11 and 12, is a top priority requiring the development of eco-friendly products and community empowerment through waste management. The Induk Pelangi Waste Bank in Siak Sri Indrapura is an active community-based waste management facility that requires support for infrastructure improvement. This program was conducted during October 2025, beginning with the identification of partner needs focused on the revitalization of the administration building. The solution was implemented through an appropriate technology approach, where the physical renovation process served as a vehicle for the application of eco-friendly natural rubber latex-based paint research. This innovative product is the result of research collaboration between Politeknik Negeri Sriwijaya PSDKU Siak and the University of Riau. The paint application was carried out in two coats in a participatory manner on the building's interior and exterior. The results show that the administration building now appears neater and more presentable. Furthermore, this activity successfully demonstrated the viability of green technology and served as an educational medium that aligns the waste bank's infrastructure with the environmental values it promotes.